An aircraft based emulation platform and control model for LEO satellite antenna beam steering - Kruger, Iwan Carel (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2010.